2010
DOI: 10.1007/s00464-010-1164-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-port laparoscopic repair of a perforated duodenal ulcer: intracorporeal “cross and twine” knotting

Abstract: Single-port laparoscopic repair using the "cross and twine" knotting technique is a feasible and safe procedure, and it may be a less invasive laparoscopic surgical technique for scarless surgical treatment of perforated duodenal ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…History of peptic ulcer disease was positive in 18% of our patients. These results are in accordance with the results of many other studies like Lee et al [15] and Ates et al [16] who reported a positive ulcer history in 23% and 14.3% of patients respectively. In our study, 54% of the patients were smokers and 26% of patients were using NSAIDs more than 2 weeks prior to the perforation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…History of peptic ulcer disease was positive in 18% of our patients. These results are in accordance with the results of many other studies like Lee et al [15] and Ates et al [16] who reported a positive ulcer history in 23% and 14.3% of patients respectively. In our study, 54% of the patients were smokers and 26% of patients were using NSAIDs more than 2 weeks prior to the perforation.…”
Section: Discussionsupporting
confidence: 93%
“…Lo et al [23] reported an operative time of 50 minutes for patients treated by ulcer closure with omental patch and 45 minutes for patients treated with simple ulcer closure only. Lee et al [15] reported a shorter operative time; only 20.7 ± 4.9 minutes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thanks to this simple approach the length of the umbilical scar remained similar to the incision used for a classic 12-mm trocar, unlike the increased incision length required for the insertion of multiple trocars through the same incision or through the same port device. 15 Our procedure took a total time of 108 minutes, with a partial laparoscopic time of 86 minutes, which was in the range of 90.2 ± 24.2 minutes reported in the series of Lee et al 13 We achieved this total and laparoscopic different time, because we needed time to get access to the peritoneal cavity. Moreover, we had to meticulously close the umbilical fascia and the separate window for the grasper at the end of the procedure.…”
Section: Discussionmentioning
confidence: 86%
“…In our case, we adopted the placement of a percutaneous stitch in the falciform ligament, increasing the exposure of the pyloric area. Another valid option is the introduction of surgical gauzes between the liver bed and upper border of the duodenum, 13 or simply the placement of a millimeter wire (Veress needle) in the right upper quadrant. 14 In SAL, usually a 5-mm optical system is used, 13,15 but in the technique described here, a 10-mm, 30°-angled scope was adopted allowing the magnification of the image and maintenance of enough pneumoperitoneum during the entire procedure.…”
Section: Discussionmentioning
confidence: 99%